Regulation of MicroRNA-497-Targeting AKT2 Influences Tumor Growth and Chemoresistance to Cisplatin in Lung Cancer - Wang, Lin; Ji, Xiang-Bo; Wang, Li-Hong; Qiu, Jian-Ge; Zhou, Feng-Mei; Liu, Wen-Jing; Wan, Di-di; Lin, Marie Chai-mi; Liu, Ling-Zhi; Zhang, Jian-Ying; Jiang, Bing-Hua (Frontiers in Cell and Developmental Biology, 2020)
Background: MicroRNA-497 (miR-497) has been implicated in several cancers. Increasing studies demonstrate the role of AKT2 in cancers as an oncogene which is closely associated with tumor aggressiveness by enhancing cancer cell survival, migration and invasion However, miR-497/AKT2 axis in non-small cell lung cancer (NSCLC) remains unclear. Methods: Quantitative real-time PCR (qRT-PCR) was used to quantify the expression of miR-497 and its target gene. The function of miR-497 in lung cancer was investigated through in vitro and in vivo assays (cell proliferation assay, cell migration assay, colony formation assay, flow cytometry assay, immunoblotting and tumorigenesis assay). Luciferase reporter assay was conducted to confirm the target gene of miR-497. Results: In this study, we found that miR-497 was significantly downregulated in tumor tissues and blood samples of lung cancer patients. To understand the potential mechanism of miR-497 in inhibiting tumor growth, we showed that miR-497 blocked the activation of AKT2 and regulated cell proliferation, cell migration, colony formation and increases chemosensitivity of H1299 cells to cisplatin by inhibiting AKT2. MiR-497 also inhibited tumor growth and suppressed expression of AKT2 at the protein and mRNA levels in mouse xenograft tumors. Conclusion: Taken together, our findings indicated that miR-497 suppresses the tumor growth by targeting AKT2, and the miR-497/AKT2 axis is a potential therapeutic target for NSCLC intervention.